2012
DOI: 10.1167/12.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Human optokinetic nystagmus: A stochastic analysis

Abstract: Optokinetic nystagmus (OKN) is a fundamental gaze-stabilizing response found in almost all vertebrates, in which eye movements attempt to compensate for the optic flow caused by self-motion. It is an alternating sequence of slow compensatory eye movements made in the direction of stimulus motion and fast eye movements made predominantly in the opposite direction. The timing and amplitude of these slow phases (SPs) and quick phases (QPs) are remarkably variable, and the cause of this variability is poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…The optokinetic response is an involuntary sawtooth movement of the eye that occurs in response to moving stimuli such as a rotating drum, or drifting bars on a computer screen [2] . The response consists of an alternating sequence of slow phases (SPs) during which the eyes track a feature of the moving stimulus, and quick phases (QPs) where the eyes move rapidly in the opposite direction to the moving stimulus [2] , [3] (see Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The optokinetic response is an involuntary sawtooth movement of the eye that occurs in response to moving stimuli such as a rotating drum, or drifting bars on a computer screen [2] . The response consists of an alternating sequence of slow phases (SPs) during which the eyes track a feature of the moving stimulus, and quick phases (QPs) where the eyes move rapidly in the opposite direction to the moving stimulus [2] , [3] (see Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The method of moments is infeasible due to poor convergence (the reciprocal Normal has no finite moments; Harris and Waddington, 2012). Maximum likelihood estimation of parameters requires vast amounts of data to distinguish between models (Waddington and Harris, 2012). There is also the problem of under-sampling at extreme values (Harris and Waddington, 2012) which is further exacerbated by the tendency of many investigators to discard “outliers.” It is easier in the rate-domain, although large data sets are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, in the contralateral bias model with strabismus, we found the L2-norm of the weights from each cortical area to the contralateral NOT to be 1.3 times greater than the L2-norm of the ipsilateral weights. Note that we cannot make a quantitative comparison between the weights estimated by Kiorpes et al and Waddington and Harris (2012) showed that the eye velocity during the slow phase increases as stimulus speed increases, but saturates at high stimulus speeds. For normal human subjects, when the stimulus speed is 10 deg/s, the slow phase eye velocity is around 8 deg/s.…”
Section: Discussionmentioning
confidence: 77%
“…The actual timing, amplitude and direction of the fast phase are variable (Waddington & Harris, 2012), rather than fixed. The fast phase of OKN also appears to take on object-targeting properties like saccades (Harrison, Freeman, & Sumner, 2014.…”
Section: Developmental Model Of the Optokinetic Reflexmentioning
confidence: 99%